Pharmacological considerations for the treatment of COVID-19 in people living with HIV (PLWH). (13th June 2021) - Gutierrez, María Del Mar; Mur, Isabel; Mateo, María Gracia; Vidal, Francesc; Domingo, Pere
ABSTRACT: Introduction: When coronavirus infectious disease-2019 (COVID-19) blew up, ill-fated auguries on the collision between COVID-19 and the human immunodeficiency virus (HIV) epidemics loomed. Areas covered: Data from observational studies suggest similar incidence attacks of SARS-CoV-2 infection in people living with HIV (PLWH) and HIV-uninfected populations. The mortality rate of COVID-19 is similar in both populations too. The authors discuss the role of combination antiretroviral therapy (cART) in preventing infection or reducing COVID-19 severity. They also discuss the pharmacological interventions for COVID-19 in PLWH. Expert opinion: Management of COVID-19 in PLWH is no different from the general population. It should be based on careful supportive care, emphasizing lung-protective ventilation, and wise pharmacological interventions. The antiviral drug remdesivir and dexamethasone are the only pharmacological interventions with clinical benefit for COVID-19, whereas anticoagulation may prevent thrombotic complications. The experience with using these drugs in PLWH is limited, which prevents from rendering well-founded conclusions. Until more data on COVID-19 in PLWH become available, the best weapons within our reach are sound supportive care and sensible use of RDV and dexamethasone, bearing in mind the potential for drug–drug interactions of most corticosteroids and antiretroviral drugs.